Steps to success : crossing the bridge between literacy research and practice - Munger, Kristen A.; Open SUNY Textbooks; BC Open Textbook Project; BCcampus (Open SUNY Textbooks, 2016)
"Steps to Success: Crossing the Bridge Between Literacy Research and Practice introduces instructional strategies linked to the most current research-supported practices in the field of literacy. The book includes chapters related to scientifically-based literacy research, early literacy development, literacy assessment, digital age influences on children's literature, literacy development in underserved student groups, secondary literacy instructional strategies, literacy and modern language, and critical discourse analysis. Chapters are written by authors with expertise in both college teaching and the delivery of research-supported literacy practices in schools. The book features detailed explanations of a wide variety of literacy strategies that can be implemented by both beginning and expert practitioners. Readers will gain knowledge about topics frequently covered in college literacy courses, along with guided practice for applying this knowledge in their future or current classrooms. The book's success-oriented framework helps guide educators toward improving their own practices and is designed to foster the literacy development of students of all ages."--BC Campus website.
1. A Brief Introduction to Literacy / Kristen A. Munger -- 2. Key Ideas for Evaluating Scientifically-Based Approaches to Literacy Instruction / Kristen A. Munger -- 3. Word Recognition Skills: One of Two Essential Components of Reading Comprehension / Maria S. Murray -- 4. Language Comprehension Ability: One of Two Essential Components of Reading Comprehension / Maria S. Murray -- 5. Types of Literacy Assessment: Principles, Procedures, and Applications / Kristen A. Munger -- 6. Approaches to Writing Instruction in Elementary Classrooms / Vicki McQuitty -- 7. Influence of the Digital Age on Children's Literature and Its Use in the Classroom / Joanna M. Robertson -- 8. Helping English Language Learners Develop Literacy Skills and Succeed Academically / Tess M. Dussling -- 9. Literacy Instruction for Students with Intellectual and Developmental Disabilities / Michelle A. Duffy -- 10. Twenty-First Century Perspectives on Adolescent Literacy and Instruction / Elizabeth C. Lewis -- 11. Teaching as a Writer--Assigning as a Reader / Bryan Ripley Crandall -- 12. Culturally Responsive Disciplinary Literacy Strategies Instruction / Kathleen A. Cullen -- 13. World Language and Literacy Learning / Joanne E. O'Toole -- 14. Teacher Discourses and Identities: Understanding Your Teaching Self / Elizabeth Y. Stevens.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on September 26, 2016).
Keywords: Literacy -- Textbooks; Electronic books